Luminous Flux and CCT Stabilization of White LED Device With a Bilevel Driver - Huanting Chen; Xiaofang Zhou; Shuo Lin; Jinhai Liu (IEEE Photonics Journal)
The optical, color, electrical, and thermal properties of an LED devices are highly dependent on one another. The luminous flux variation and correlated color temperature (CCT) shifting of white LED sources is attributed to luminous efficacy and emission spectrum shifting with the electrical power and heat-dissipation power. An analysis model that includes the luminous flux, CCT, electrical power, and junction temperature of the white LED sources with bilevel driver is proposed in this paper. The proposed model can descript that the stablized luminous flux and CCT of the white LED system with bilevel driver is a result of the complex interactions among the given electrical power of bilevel, duty cycle, thermal resistances, junction temperature, and the physical parameters of the LED sources. Reduction variation of CCT and luminous flux of the white LED device with bilevel driver over a dimming range has been practically achieved. The proposed method can be easily adopted for improving the CCT and luminous flux stabilization of the white LED device with a bilevel driver.